ChemInform Abstract: Asymmetric Domino Synthesis of Indanes Bearing Four Contiguous Stereocenters Catalyzed by Sub‐Mol% Loadings of a Squaramide in Minutes. Issue 9 (4th March 2014) - Loh, Charles C. J.; Hack, Daniel; Enders, Dieter
Abstract An organocatalytic Michael—Henry domino reaction affording polyfunctionalized indane derivatives (III) with high diastereo‐ and enantioselectivity is reported.